2007
DOI: 10.1002/mame.200600306
|View full text |Cite
|
Sign up to set email alerts
|

Phenylethynyl End‐Capped Fluorinated Imide Oligomer AFR‐PEPA‐N: Morphology and Processibility Characteristics

Abstract: Two phenylethynyl phthalic anhydride‐capped imide oligomers, AFR‐PEPA‐2 and AFR‐PEPA‐8, with molecular weights of 1 601 and 4 699 g · mol−1, respectively, were synthesized and characterized. The AFR‐PEPA‐N oligomers show higher glass transition temperatures and higher thermal decomposition temperatures than phenylethynyl‐terminated imide PETI‐5. After curing for 1 h at 390 °C, AFR‐PEPA‐2 and AFR‐PEPA‐8 have Tgs of 370 and 358 °C, respectively. AFR‐PEPA‐N oligomers demonstrated lower minimum complex melt viscos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…AI‐n0 (repeat unit n = 0) was one component in m ‐AI as shown in GPC curve of Figure 3 and was demonstrated to have crystal phase by XRD in Figure 4. The same phenomenon could be seen for other low‐molecular weight polyimide oligomers 47, 50, 51. After m ‐AI and p ‐AI were cured, m ‐API (cured m ‐AI) and p ‐API (cured p ‐AI) were amorphous as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…AI‐n0 (repeat unit n = 0) was one component in m ‐AI as shown in GPC curve of Figure 3 and was demonstrated to have crystal phase by XRD in Figure 4. The same phenomenon could be seen for other low‐molecular weight polyimide oligomers 47, 50, 51. After m ‐AI and p ‐AI were cured, m ‐API (cured m ‐AI) and p ‐API (cured p ‐AI) were amorphous as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
“…To balance the high temperature performance, high hydrolytic resistance and the processing ease of these materials, the exploration of new compositions and new processing methods for polyimides are developing rapidly. Many researchers have demonstrated that termination of various imide oligomers with phenylethynylg roups can lead to dramatic improvements in hydrothermal durability, toughness and processability [3][4][5][6]. The commonly used terminated agent was 4-(phenylethynyl)phthalic anhydride.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fiber‐reinforced, high‐temperature, polymer‐matrix composites are particularly attractive for aerospace structures because of their low density [2, 3], high mechanical strength [2, 4–10], high modulus [2, 4, 6, 8, 9], thermo‐oxidative stability [2, 4, 9, 11, 12], electrical properties [2, 6, 10, 13], and excellent chemical resistance [2, 5, 6, 14]. Various polyimide‐based composites have been studied for use in aerospace applications for these reasons [2, 4, 6, 11, 15]. Phenylethynyl‐endcapped fluorinated polyimides are especially useful because of their environmental stability and high glass‐transition temperature ( T g ) (435–455°C) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Blistering, in particular, occurs when there is enough moisture pressure to exceed the strength of the material, which happens when the temperature and water content is high [6, 17]. In general, polyimides are very thermally stable and have characteristically high T g s and decomposition temperatures [15], but their uptake of moisture needs further study, especially for fluorinated polyimides, because of initial findings with similar polyimides (PMR‐II‐50, AFR700B, and PETI‐5) [3, 16–19]. Adding reinforcements to a neat polyimide resin, such as carbon‐fiber, has been shown to improve the hygrothermal degradation of the composite material [19, 21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation